Legal Formality and its Impact on the Binding and Enforceability of the Contract in Jordanian Jurisprudence and Law: An Applied Study on the Sales Contract and the Marriage Contract - Al Shdeifat, Areej Amin (Dirasat: Shari’a and Law Sciences, 2025)
Objectives: This research aims to establish the legitimacy of requiring specific formalities in contracts, examining their applications in Islamic jurisprudence and contemporary civil law. It clarifies which transactions require formality and which do not, and explains the role of customary practice in recognizing legal formalities. Additionally, it demonstrates the impact of these formalities on contracts, determining when they are essential for contract formation and when they are procedural requirements for enforcement. Methods: The research employs three methodologies: inductive, analytical, and comparative. It traces scholarly and legal sources to analyze the expression of intent based on customary practice. It also compares legal outcomes in Islamic jurisprudence with those after imposing specific formal requirements. Results: The research shows that requiring specific formalities for contracts is supported by Islamic legal evidence and established practices among scholars. In Jordanian law, contractual formalities are required only for specific transactions, not for all contracts. Transactions based on mutual consent and material exchanges do not require particular formalities. The study reveals that expressing intent without official registration is merely a promise, not a contract, and does not produce contractual effects. This is because formal contractual requirements are widely recognized and customary, and anything less is considered a proposal that can be withdrawn without legal consequences. Examples such as sales and marriage contracts illustrate this concept. Conclusions: There is a need to enhance the role of fatwa (legal opinions) in issuing rulings that align with comparative customary practices.